Características familiares asociadas a ideación suicida en estudiantes de tres instituciones educativas públicas de Iquitos 2023 - Cárdenas Arellano, Jorge (2024)
The Suicidal conduct among adolescents is a concerning issue ranging from thoughts to concrete acts of self-destruction. Recognizing this problem and identifying risk factors are essential to promote healthy family environments for its prevention. Therefore, this study aims to determine the family characteristics associated with suicidal ideation in students from three public educational institutions in Iquitos 2023. A correlational, prospective, non experimental study was conducted with a sample of 233 students. It was concluded that the prevalence of suicidal ideation was 21.0%. It was observed that the educational and occupational level of parents, as well as religion and family functioning, did not show a significant association with suicidal ideation (p>0.05). However, it was observed that females were 2.2 times more likely to experience suicidal ideation. Living with both parents was associated with a 50% lower probability of suicidal ideation, as well as belonging to a nuclear family. Family history of suicide attempts increased the risk by 3.5 times, while lack of communication with parents and family conflicts increased the risk by 4 and 5.8 times, respectively.